(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical, paraclinical and intraoperative characteristics, and to evaluate intraoperative blood loss and factors associated with blood loss ≥500 mL in pregnant women undergoing cesarean delivery with a previous cesarean scar. Subject and method: This analytical cross-sectional study included 402 pregnant women with a previous cesarean scar who underwent cesarean delivery at Can Tho Central General Hospital from July 2024 to January 2026. Blood loss was quantitatively measured using a calibrated collection drape, suctioned volume after subtraction of amniotic fluid and irrigation fluid, and converted surgical gauze weight based on the dry–wet weighing method. Results: The mean maternal age was 31.16 ± 5.61 years. Most women had one previous cesarean delivery (71.64%) and an interdelivery interval >24 months (85.57%). The mean intraoperative blood loss was 402.94 ± 143.28 mL. Blood loss of 500–<1000 mL accounted for 15.42%, while blood loss ≥1000 mL accounted for 0.75%. After adjustment, maternal age ≥35 years, preoperative anemia, pelvic adhesions, abnormal placentation, uterine fibroids and estimated fetal weight ≥3500 g were associated with blood loss ≥500 mL. Conclusion: Intraoperative blood loss during cesarean delivery in pregnant women with a previous cesarean scar was predominantly <500 mL. Maternal age ≥35 years, preoperative anemia and estimated fetal weight ≥3500 g should be considered before surgery. Intraoperatively, pelvic adhesions, abnormal placentation and concomitant uterine fibroids should be carefully assessed when evaluating the risk of increased blood loss in this population.